PPARG, AGTR1, CXCL16 and LGALS2 polymorphisms are correlated with the risk for coronary heart disease - Tian, Jianwei (Int J Clin Exp Pathol, 2015)
Purpose: Our study was designed to explore the interaction between genes of PPARG, AGTR1, CXCL16 and LGALS2 and further investigate the association between genes polymorphisms and coronary heart disease (CHD). Methods: 90 CHD patients and 80 healthy individuals were enrolled in our study. Gene chip technology was used for checking four single nucleotide polymorphisms (SNPs) (PPARG rs1152002, AGTR1 rs5186, CXCL16 rs3744700 and LGALS2 rs7291467). MDR software was used to analyze gene-gene interactions. Odds ratio (OR) with 95% confidence interval (CI) were employed to evaluate the association of genes and CHD risk. Results: Genotypes and alleles distribution in case and control groups showed significant difference (P<0.05). And there exists interaction among genes. The model of PPARG×CXCL16 showed effects on the occurrence of CHD (OR=2.92, 95% CI=1.44-5.94). Meanwhile, the PPARG×AGTR1×CXCL16×LGALS2 model was associated with CHD susceptibility (OR=3.97, 95% CI=2.01-7.84). Moreover, we found that PPARG×LGALS2×CXCL16, was the best interaction model and it could significantly increase the risk for CHD (OR=3.37, 95% CI=1.71-6.63). Conclusion: PPARG rs1152002, AGTR1 rs5186, CXCL16 rs3744700 and LGALS2 rs7291467 polymorphisms may be closely related to the development of CHD. Moreover, there exist gene-gene interactions among these susceptibility genes.